O conflito entre a proteção ao trabalho e a proteção ao consumidor: reflexos da nova competência da justiça do trabalho - Barros, Daniel Conde (2008)
This study aims to discuss the conflict brought from the issue of constitutional amendment No. 45 of relationship between the concept of consumption and the labor relationship. The extension of jurisdiction of the justice of work has brought to light the possibility to exist in the same legal relationship, labour relations that were also relations of consumption, leading to trial, then, the Justice Labour, these relations. To this end, trying to, initially, to examine the reform itself, its functioning and purpose, and the object of protection. Since then, relate the nature of such standards with the role of the state, bringing thus the degree of importance of these standards in the legal system. The kind of fundamental right of standards that protect the employment relations and relations of consumption make the course that all must follow the interpretation, always searching for its most complete realization and affirmation. Then looked up the context of the current world of work, establishing the legal limits imposed on constitutional reform from the “substancialista” design of incorporation, as well as its effect on private relationships. Finally, looked up the definition of essential elements for each type of relationship, considering the need to differentiate, depending on the subject in each protected species have unique situations that determine a treatment distinct.